Architecture of the centriole cartwheel‐containing region revealed by cryo‐electron tomography. (20th September 2020) - Klena, Nikolai; Le Guennec, Maeva; Tassin, Anne‐Marie; van den Hoek, Hugo; Erdmann, Philipp S; Schaffer, Miroslava; Geimer, Stefan; Aeschlimann, Gabriel; Kovacik, Lubomir; Sadian, Yashar; Goldie, Kenneth N; Stahlberg, Henning; et al.
Abstract: Centrioles are evolutionarily conserved barrels of microtubule triplets that form the core of the centrosome and the base of the cilium. While the crucial role of the proximal region in centriole biogenesis has been well documented, its native architecture and evolutionary conservation remain relatively unexplored. Here, using cryo‐electron tomography of centrioles from four evolutionarily distant species, we report on the architectural diversity of the centriole's proximal cartwheel‐bearing region. Our work reveals that the cartwheel central hub is constructed from a stack of paired rings with cartwheel inner densities inside. In both Paramecium and Chlamydomonas, the repeating structural unit of the cartwheel has a periodicity of 25 nm and consists of three ring pairs, with 6 radial spokes emanating and merging into a single bundle that connects to the microtubule triplet via the D2‐rod and the pinhead. Finally, we identified that the cartwheel is indirectly connected to the A‐C linker through the triplet base structure extending from the pinhead. Together, our work provides unprecedented evolutionary insights into the architecture of the centriole proximal region, which underlies centriole biogenesis. Synopsis: The centriole's intricate architecture underlies its crucial role in assembly of centrosomes and cilia/flagellae. Here, in situ and ex vivo cryo‐electron tomography of centrioles from Chlamydomonas, Paramecium, Naegleria and humans provides architectural maps of the centriole's proximal region and reveals evolutionarily‐conserved structures as well as differences between species. The cartwheel central hub is an evolutionarily‐conserved stack of ring pairs. Cartwheel inner densities (CID) are present in Trichonympha, human, Paramecium, Chlamydomonas and Naegleria centrioles. Cartwheel radial spokes are polarized, with spoke architecture diverging between species. The A‐C linker is connected to the pinhead through the triplet base. Structural elements in the proximal region are specifically positioned relative to each other, with clear boundaries and overlaps. Abstract : In situ and ex vivo cryo‐ET of centrioles from Chlamydomonas, Paramecium, Naegleria and humans describe the centriole's proximal region and reveal evolutionarily‐conserved structures as well as differences between species.